2013
DOI: 10.1016/j.nlm.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

d-cycloserine in the basolateral amygdala prevents extinction and enhances reconsolidation of odor-reward associative learning in rats

Abstract: It is well established that D-cycloserine (DCS), a partial agonist of the NMDA receptor glycine site, enhances learning and memory processes. Although the effects of DCS have been especially elucidated in the extinction and reconsolidation of aversive behavioral paradigms or drug-related behaviors, they have not been clearly determined in appetitive tasks using natural reinforcers. The current study examined the effects of pre-retrieval intra-basolateral amygdala (BLA) infusions of DCS on the extinction and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In this regard, there is evidence showing, on the one hand, that DCS facilitated ODT [15], conditioned fear responses [64], [65], [66], conditioned flavor-taste preference and conditioned-taste aversion [13], [67], or procedural learning in humans [68]. On the other hand, no facilitative effects of DCS administration were found in the retention of Morris water maze (MWM) learning in rodents [69], [70], or declarative word-pair learning in humans [68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, there is evidence showing, on the one hand, that DCS facilitated ODT [15], conditioned fear responses [64], [65], [66], conditioned flavor-taste preference and conditioned-taste aversion [13], [67], or procedural learning in humans [68]. On the other hand, no facilitative effects of DCS administration were found in the retention of Morris water maze (MWM) learning in rodents [69], [70], or declarative word-pair learning in humans [68].…”
Section: Discussionmentioning
confidence: 99%
“…The DCS dosage, for example, may not have been optimal, which is an important factor in that the therapeutic window for DCS to enhance human fear memory extinction has been reported as narrow [78]. In this respect, although the previous studies testing intracerebral DCS administration used the same dosage (10 µg/site) [15], [31], [79], [80], [81], higher doses might have been more appropriate to find enhancing effects in VEH rats. Indeed, it has been reported that only a higher dose of systemic DCS was able to promote episodic-like memory [61], although lower doses potentiated memory in non-relational aversive paradigms [82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total volume of drug used was 1.0ml/kg, or an equivalent amount of SAL, in all cases. For intra-BLA infusion, DCS was dissolved in SAL to a final concentration of 40 µg/µl and the amount infused was 10 µg/side (Lee et al, 2009;Portero-Tresserra et al, 2013).…”
Section: Drugs and Administrationmentioning
confidence: 99%
“…The amygdala appears to be necessary for processes that involve updating of representations of value, not only in fear extinction, but also in reinforcer devaluation (Morrison and Salzman, 2010). Accordingly, amygdala participation in appetitive extinction has been demonstrated for food-reward extinction learning (Judice-Daher et al, 2012;Portero-Tresserra et al, 2013), for extinction of responding to a visual CS which had been paired with food reward (Lindgren et al, 2003). Recent neuroimaging studies suggest that the human amygdala is involved in many reward-based decision-making tasks (Morrison and Salzman, 2010).…”
Section: Introductionmentioning
confidence: 99%